The Effect of Implementation of the Learning Policies to Learning Management in Realizing Student’s Learning Outcomes (Reseach at Ma Nurul Huda Cibojong Cisurupan Garut) - Iska Fatmawati; Abdusy Syakur Amin; Ijudin (al-Afkar, Journal For Islamic Studies, 2024)
Education is crucial to the growth of the individual as well as the society. In light of this, the government is fully committed to giving the education sector its full attention in the hopes that a well-functioning educational system will produce a future generation of citizens with moral character and the capacity to engage with society on a local, national, and international level. The low quality of education remains a significant issue in madrasah education. Suboptimal learning management is one of the causes of suboptimal curriculum implementation, leading to suboptimal student learning outcomes. This study aims to analyze the implementation of curriculum policy on learning management to achieve student learning outcomes. The research method used in this study is a descriptive analysis method with observation techniques, survey techniques, interview techniques, and documentation study techniques. The data analysis technique used to answer the hypotheses of the study is statistics with path analysis models. The population and respondents of this study are educators at Madrasah Aliyah Nurul Huda Cibojong Cisurupan Garut, totaling 47 respondents. The results of the main hypothesis testing using path analysis are "There is an Influence of Curriculum Policy Implementation on Learning Management to Achieve Student Learning Outcomes." Based on the results of the test using SPSS 23, the F-value is higher than the Ftable (20.140 > 2.430) with a significance value of (0.000 < 0.05), indicating that the implementation of curriculum policy has an effect on learning management to achieve student learning outcomes. With the R square test or coefficient of determination, the obtained R square value is 0.478 with an Adjusted R Square value of 0.454. It can be explained that the contribution of curriculum policy implementation and learning management to student learning outcomes is 45.4%, while the remaining 54.6% is influenced by other factors not examined. The recommendations in this study are as follows: First, for the variable of curriculum policy implementation, there should be proper guidance and good cooperation to ensure effective curriculum policy implementation. Second, for the variable of learning management, a collaborative approach, provision of resources and support, clear communication, and explanation are needed. Third, for the variable of learning outcomes, teachers can implement learning strategies such as group discussions, project-based assignments, case analysis, debates, and others. These strategies should be applied consistently and provide opportunities for students to practice and develop their skills.